2017
DOI: 10.1007/s11999-016-4981-2
|View full text |Cite|
|
Sign up to set email alerts
|

What Is the Natural History of Asymptomatic Pseudotumors in Metal-on-metal THAs at Mid-term Followup?

Abstract: Background The risk of early revision because of pseudotumors in patients who have undergone large-head metal-on-metal (MoM) total hip arthroplasty (THA) is well documented. However, the natural history of asymptomatic pseudotumors or of MoM articulations without pseudotumors is less well understood. The aim of our study was to investigate the natural history of primary MoM THA at mid-term followup. Questions/purposes The purposes of this study were: (1) Did previously detected pseudotumors persist or worsen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
18
0
3
Order By: Relevance
“…The incidence of pseudotumor following MoM THA differs from detection methods in the literature. Konan et al [ 11 ] indicated that the incidence of asymptomatic pseudotumors is as high as 32% in patients who underwent a MoM THA after ultrasound examination at early follow-up. However, most of asymptomatic pseudotumors with an early positive ultrasound scan remain asymptomatic at interval follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pseudotumor following MoM THA differs from detection methods in the literature. Konan et al [ 11 ] indicated that the incidence of asymptomatic pseudotumors is as high as 32% in patients who underwent a MoM THA after ultrasound examination at early follow-up. However, most of asymptomatic pseudotumors with an early positive ultrasound scan remain asymptomatic at interval follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Так, M.H. Hjorth et al отмечают развитие осложнений в 19,5% случаев [8], тогда как S. Konan et al регистрируют 32% осложнений [9]. Локальные осложнения пары трения металл-металл проявляются в виде грануляционных разрастаний в ответ на металлические частицы [10][11][12].…”
Section: локальные осложненияunclassified
“…Более того, во всех описанных 10 случаях была выявлена нестабильность эндопротезов, в связи с которой износ эндопротезов был повышен, и, как следствие, возникало значительное повышение уровня ионов кобальта в крови. Системные проявления в этих случаях были следующие: неврологические (13 случаев), кардиальные (10), со стороны щитовидной железы (9). В литературе описан только 1 случай летального исхода, вызванной токсичностью ионов кобальта, в результате которой у пациента развилась дилатационная кардиомиопатия и полиорганная недостаточность, которые прогрессировали даже после ревизии с удалением эндопротеза [20; 21].…”
Section: системные осложненияunclassified
“…At present, various types of cementless femoral prosthesis have been widely used by surgeons [15][16][17]. It has been demonstrated that proximal coated single-wedge new stems (for example, the M/L Taper stem, Tri-Lock stem) optimize the tapered wedge fixation while providing secure mediolateral stability.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that proximal coated single-wedge new stems (for example, the M/L Taper stem, Tri-Lock stem) optimize the tapered wedge fixation while providing secure mediolateral stability. The proximal circumferential coating of the stem facilitates mechanical fixation for a secure bone-implant interface [15]. The fully coated dual-wedge classic stems (for example, the LCU stem and Corail stem) are characterized by a dual-wedge design with a rectangular cross-section to ensure the femoral prosthesis proximal stability.…”
Section: Introductionmentioning
confidence: 99%